Relaunching Strategy and Consumer Repurchase Behavior: Case Study of Ranchmarket Galaxy Surabaya - Koentjoro, Eduard; Teofilus; Utami, Whidya (Manunggal Halim Jaya, 2026)
The rapid growth of specialty retail has encouraged conventional supermarkets to innovate, particularly in enhancing the in-store experience. Ranchmarket Galaxy Surabaya adopted a store relaunching strategy that included changes in layout, product display, visual merchandising, in-store promotions, and staff service. However, its implementation faced challenges such as limited supplier support, insufficient promotional funds, and weak communication of promotional programs. This study explores the effect of store relaunching elements on consumer repurchase behavior using a qualitative case study approach. Data were collected through semi-structured interviews and online questionnaires with 20 consumers who had visited the store after the relaunch. The Stimulus–Organism–Response (S-O-R) framework was applied to analyze how physical and promotional stimuli influence consumer perceptions and trigger behavioral responses. The findings show that appealing visual merchandising, smoother store navigation, effective bundling promotions, and proactive staff service collectively shape positive perceptions, strengthen emotional attachment, and encourage repeat purchases. Nevertheless, the study is limited by its small sample size and single-location focus, which restricts the generalization of results. Future research should involve larger samples and comparative studies across different retail formats.